Implementasi Aplikasi Pelaporan Pelayanan Publik Berbasis Android Pada Ombudsman Di Provinsi Banten - Alldy Maulana; Sofa Sofiana (Journal Of Informatics And Busisnes, 2025)
The Banten Province Ombudsman Institution currently still relies on receiving reporting and monitoring carried out by the public regarding forms of public services that are still manual. This means that the public in this case must come directly to the ombudsman institution. This shows that effective and efficient public services have not been created on the basis of being fast, precise and low cost. The aim of this research is to design a public service reporting application that carries out Android-based maladministration. The type of research used is the waterfall method. This application runs on the Android operating system. Based on the research results, this application can be used to help and make it easier for the public to report legal violations and dissatisfaction with public services carried out by state institutions, both government institutions, including State-Owned Enterprises (BUMN), State-Owned Legal Entities ( BHMN) and Regional Owned Enterprises (BUMD) as public service providers who carry out their duties and functions in accordance with the rules and regulations applicable to the Ombudsman quickly, efficiently and at low cost.